Tư duy nghịch lý và áp lực học tập thúc đẩy sự sáng tạo và kết quả công việc của nhân viên: Nghiên cứu trong lĩnh vực dịch vụ ngân hàng tại Việt Nam - Võ Thành , Đức; Trần Hà Minh , Quân (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2021)
Applying paradox theory, this study investigates the impact of learning tension, paradox mindset, and the interaction between them on employee creativity, subsequently leading to enhance in-role performance. Based on a data set of 430 service employees in the banking industry, this study found that employee creativity mediated the relationship between learning tension and in-role performance. Additionally, employee creativity mediated the relationship between paradox mindset and in-role performance. The interaction between learning tension and paradox mindset on employee creativity, however, was not significant. These results contributed to the literature on employee creativity by finding two antecedents, learning tension and paradox mindset. The findings of this study confirm the applicability of the paradox theory to explain employee creativity in emerging markets like Vietnam.
Keywords: Learning tension; Paradox mindset; Employee creativity; In-role performance